Altered stability of pulmonary surfactant in SP-C-deficient mice - Glasser, Stephan W. (The National Academy of Sciences, 2001)
The surfactant protein C (SP-C) gene encodes an extremely hydrophobic, 4-kDa peptide produced by alveolar epithelial cells in the lung. To discern the role of SP-C in lung function, SP-C-deficient (−/−) mice were produced. The SP-C (−/−) mice were viable at birth and grew normally to adulthood without apparent pulmonary abnormalities. SP-C mRNA was not detected in the lungs of SP-C (−/−) mice, nor was mature SP-C protein detected by Western blot of alveolar lavage from SP-C (−/−) mice. The levels of the other surfactant proteins (A, B, D) in alveolar lavage were comparable to those in wild-type mice. Surfactant pool sizes, surfactant synthesis, and lung morphology were similar in SP-C (−/−) and SP-C (+/+) mice. Lamellar bodies were present in SP-C (−/−) type II cells, and tubular myelin was present in the alveolar lumen. Lung mechanics studies demonstrated abnormalities in lung hysteresivity (a term used to reflect the mechanical coupling between energy dissipative forces and tissue-elastic properties) at low, positive-end, expiratory pressures. The stability of captive bubbles with surfactant from the SP-C (−/−) mice was decreased significantly, indicating that SP-C plays a role in the stabilization of surfactant at low lung volumes, a condition that may accompany respiratory distress syndrome in infants and adults.